2017
DOI: 10.1007/s13593-017-0433-y
|View full text |Cite
|
Sign up to set email alerts
|

Farming with alternative pollinators increases yields and incomes of cucumber and sour cherry

Abstract: Pollinator decline is acknowledged worldwide and constitutes a major subject of environmental research. Nevertheless, farmers' efforts to protect pollinators in agricultural lands remain very limited, in particular if no compensation scheme is applicable. Current research focuses on measuring pollinator diversity in different landscapes, but research on income gains, due to habitat enhancement and high pollinator diversity, may have greater potential to induce farmers' field management changes. In 2012, it was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
67
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 30 publications
(71 citation statements)
references
References 24 publications
3
67
0
1
Order By: Relevance
“…Alternative to individual counterproductive coping strategies, governments can enhance their policies and can start timely restoration of agricultural lands for pollinators e.g. by introducing farming with alternative pollinators (FAP; Christmann & Aw‐Hassan ; Christmann et al ; Christmann ) or paying rewards for seeding wildflower strips.…”
Section: Implications For Restoration Effortsmentioning
confidence: 99%
See 3 more Smart Citations
“…Alternative to individual counterproductive coping strategies, governments can enhance their policies and can start timely restoration of agricultural lands for pollinators e.g. by introducing farming with alternative pollinators (FAP; Christmann & Aw‐Hassan ; Christmann et al ; Christmann ) or paying rewards for seeding wildflower strips.…”
Section: Implications For Restoration Effortsmentioning
confidence: 99%
“…Pollinators are in decline on all continents (except Antarctica, which does not host them; Hassan et al ) due to habitat loss, agricultural practices, climate change (Biesmeijer et al ; Burkle et al ; Dirzo et al ; Goulson ; IPBES ; Potts et al , ; Hallmann et al ; Ashbacher ; Glaum ; Hallmann et al ; Sánchez‐Bayo & Wyckhuys ; Schweiger et al ), and common lack of knowledge among farmers (Kasina et al ; Munyuli ; Hanes et al ; Christmann et al ). Dainese et al () showed that richness of service providers such as pollinators has higher positive impacts than their abundance.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Farming with Alternative Pollinators is a new approach with a limited number of field experiments in Uzbekistan and currently Morocco. The pilot project in Uzbekistan (main crops: cucumber and sour cherry; partly faba bean and partly sainfoin in the habitat zone; Christmann et al, 2014 , in review) did on-farm trials mainly with smallholders, because in general they use less or no agricultural chemicals as they prefer low production costs and healthy food for their own families. Trials with smallholders can develop first data to convince commercial farmers too.…”
Section: General Approaches To Encourage the Synergy Between Food Promentioning
confidence: 99%